Social Media in Supreme Audit Institution: Systematic Literature Review with a Narrative Approach - Suprapto, Prihandana Aditiyando; Suwaryono, Ixora Lundia (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This paper conducts a systematic literature review (SLR) to examine how Supreme Audit Institutions (SAIs) have integrated social media as a means to promote transparency, accountability, and public engagement. Based on an analysis of twenty two scholarly publications released between 2008 and 2024, the study highlights patterns in the adoption and application of social media platforms particularly on Twitter and Facebook within the context of government audits. Findings indicate that although SAIs increasingly utilize these platforms to disseminate information and enhance public outreach, their communication strategies often fall short of fostering meaningful, interactive engagement with citizens. Common obstacles include institutional conservatism, limited resources, and the complexity of audit language, all of which hinder broader participation. Nonetheless, the literature identifies emerging best practices that demonstrate how strategic use of social media can move beyond passive information sharing to support dialogue, responsiveness, and collaborative oversight. The review concludes that social media holds considerable yet largely untapped potential to strengthen SAIs’ democratic function. Realizing this potential will require not only technological adaptation but also organizational shifts toward more open, participatory governance models.